Experimental review of PEI electrodeposition onto copper substrates for insulation of complex geometries. Issue 55 (26th October 2021) - Zirignon, J.-C.; Capezza, A. J.; Xiao, X.; Andersson, R. L.; Forslund, M.; Dinér, P.; Olsson, R. T.
Abstract : Electrophoretic deposition relying on electrodeposition of charged polymers via modulated electrical fields is reported. Superior surface finishes that could pass a dielectric withstand test at 10 kV mm −1 were obtained for pulsed potentials at 20 V. Abstract : Polyetherimide (PEI) was used for coating copper substrates via electrophoretic deposition (EPD) for electrical insulation. Different substrate preparation and electrical field application techniques were compared, demonstrating that the use of a pulsed voltage of 20 V allowed for the best formation of insulating coatings in the 2–6 μm thickness range. The results indicate that pulsed EPD is the best technique to effectively coat conductive substrates with superior surface finish coatings that could pass a dielectric withstand test at 10 kV mm −1, which is of importance within the EV automotive industry.